SOLVING COMMUNITY PROBLEMS WITH STUDENT PARTICIPATION IN LEYAO VILLAGE, KWANDANG DISTRICT, NORTH GORONTALO DISTRICT - Suherman, Sutianto Pratama; Baruadi, Alfi Sahri R (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2024)
Every village has obstacles and needs solutions, some of the problem solving in the village is carried out with various approaches, one of which is a participatory approach. The participatory method carried out in Leyao Village uses 4 stages consisting of the observation stage, the meeting or discussion stage, the activity stage and the evaluation stage. From the results of the meeting, it was found that there were 3 problems in Leyao Village, namely river abrasion and flooding, structuring residents' houses, structuring village and hamlet boundaries. The solutions given are in the form of planting bamboo trees on the banks of the river, making village boundaries and numbering residents' houses.